The Japanese in Ryokan : (Shufunotomo Co., Ltd., 1985)
In the ryokan, the traditional Japanese guesthouse, building and landscape are melded in harmonic unity. Art, architecture, and the culture of daily life in ancient Japan as well as ceremonies and rituals, including the tea ceremony, the way of the Samurai, and much more is elucidated and explored in richly illustrated articles.